Evolutionary Emotion Theory in Second Language Education - Stern, Joseph (2014)
After a long period of neglect, research into emotion has accelerated over the past several decades, producing many findings and theories that could be useful in educational practice. This study focuses on the most recent research into ultimate explanations of affect, which evolutionary psychology, unlike the schools of thought that currently predominate in educational theory, can provide. This study seeks to provide context for an evolutionary view of affect through a survey of emotion theories and a discussion of how they have influenced educational practices, before turning to evolutionary psychology, and its educational and emotion theory. It lays out three potential applications for evolutionary psychology’s emotion theory in the second language classroom, and assesses their plausibility through three research instruments. Findings indicate that there is support for two out of the three applications. Directions for the future research and development of these applications are discussed in the final chapter.